Beyond music: The socially responsible legacy of the EXIT Foundation: A retrospective study - Istijanović Lenka; Manevska Ivana (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo)
Corporate social responsibility (CSR) is a term used to describe strategies companies apply to make them more ethical and friendly towards the community. The subject whose CSR activities proved to be of special interest, because of the scope of their influence, is the EXIT Foundation, the official organizer of the famous EXIT Festival, which has been held at the Petrovaradin Fortress in Novi Sad, Serbia since 2000. On the tenth anniversary of the founding of the EXIT Foundation, it was decided to conduct a retrospective analysis of the socially responsible activities conducted by this foundation. This analysis aimed to determine what types of CSR activities were conducted by the Foundation to pinpoint the main field of action, what fields were neglected, and to whom further attention should be given in the future. The multidimensional approach of implemented socially responsible initiatives made it impossible to identify a key field that could potentially be considered the focus of the CRS activities of the EXIT Foundation. However, based on the impact achieved by the festival itself, the need to focus future initiatives on the dimension of environmental protection was identified.